Dampak Desentralisasi Fiskal terhadap Disparitas Akses Pendidikan Dasar di Indonesia - Doriza, Shinta; Purwanto, Deniey A.; Maulida, Ernita (UI Scholars Hub, 2012)
The objective of fiscal decentralization objective in Indonesia is to reduce development disparities. Regarding education development, one crucial issue is access disparity. Using 440 sub provincial database during 2005-2009, this study is aim to analyze the impact of fiscal decentralization in reducing disparity of primary education access. Using fixed-effect model, the result showed that Dana Alokasi Khusus (DAK) for Education, DAK Non Education, and Pendapatan Asli Daerah (PAD) have significant impact in reducing education access disparity along with the wealth and regional characteristics. Nonetheless efforts need to be done to optimize the equalization of education access including strengthening the provincial government role in resources allocation and distribution of basic education services.